Non-invasive diagnosis of liver fibrosis in children with chronic hepatitis B by transient elastography - Sayma Rahman Munmun; Mohammad Rukunuzzaman; Mohammad Wahiduzzaman Mazumder; Archana Shrestha Yadav; Luthfun Nahar; Mohammad Benzamin; Abu Sayed Mohammad Bazlul Karim (Paediatrica Indonesiana, 2023)
Background Chronic hepatitis B (CHB) is one of the most alarming global health problems. Children with CHB mostly remain asymptomatic but serious sequelae like cirrhosis and hepatocellular carcinoma may develop at any age. Liver biopsy, despite being the gold standard, is not preferable for the diagnosis of liver fibrosis because it is invasive and painful. Transient elastography, a noninvasive marker for fibrosis, could play an important role in this disease. Objective To observe the role of transient elastography in the assessment of the progression of liver damage in children with chronic hepatitis B. Methods This cross-sectional study was conducted at The Department of Paediatric Gastroenterology and Nutrition of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Based on the inclusion and exclusion criteria, there were a total of 55 cases of CHB. Besides proper clinical history, physical examination, and initial investigation, transient elastography was performed in all of the cases. Liver biopsy was taken in 20 patients with raised serum ALT level after taking proper consent. Elastographic findings were compared with clinical, biochemical, virological, and histological findings. Results The mean age was 11.46 (SD 3.6) years and 68.7% were male. Most (65.4%) of the patients were asymptomatic at presentation and biochemically normal. Liver stiffness measurements had positive but insignificant correlation with liver biopsy (r=0.43, P=0.06). Sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy for transient elastography were 80%, 53.3%, 36.3%, 88%, and 60% respectively. Areas under the ROC curve were 0.76 (95%CI 0.47 to 1.0) for patients with significant fibrosis (F? 2). Using a cut off value of 8.05 kPa, patients with significant fibrosis were detected with a sensitivity, specificity of 80% and 53%, respectively. Findings of transient elastography were significantly associated with clinical findings like anaemia, jaundice, hepatosplenomegaly, stigmata of CLD and biochemical findings like serum ALT, AST as well as virological parameters. Conclusion Transient elastography has a limited role in confirming a diagnosis of significant fibrosis. But because of good sensitivity, transient elastography can be used as an initial presumptive diagnostic tool for assessing significant hepatic fibrosis. A cut off value of less than 8.05 in transient elastography can be used for exclusion of significant fibrosis.